Psychometric Validation of the Hepatitis C Symptom and Impact Questionnaire (HCV-SIQv4) in a Diverse Sample of Adults with Chronic Hepatitis C Virus Infection Treated with an Interferon-free Simeprevir-containing Regimen - Andrew Trigg; Eric Chan; Helen Kitchen; Tom Willgoss; Kai Fai Ho; Renee Pierson; Jane Scott (Journal of Health Economics and Outcomes Research)
**Background:** Hepatitis C virus (HCV) infection and its treatments are associated with significant symptoms, side effects and impact on patients functioning. The Hepatitis C Symptom and Impact Questionnaire version 4 (HCV-SIQv4) was developed according to FDA Patient Reported Outcomes (PRO) Guidance, for evaluating chronic HCV infection and its treatment.